Following Cu Microstructure Evolution in CuZnO/Al2O3(−Cs) Catalysts During Activation in H2 using in situ XRD and XRD‐CT. Issue 1 (21st December 2022) - Farmer, Daniela M.; Jacques, Simon D. M.; Waller, David; Boullosa Eiras, Sara; Roy, Kanak; Held, Georg; Sankar, Gopinathan; Beale, Andrew M.
Abstract: Invited for this month's cover is the group of Andrew M. Beale at the University College London and at the Research Complex at Harwell (UK). The cover picture demonstrates how X‐rays can be used to obtain spatially resolved chemical imaging insight from within an industrial catalytic reactor. Understanding how the microstructure of the active Cu 0 component in the commercially applicable Cu/ZnO/Al2 O3 (−Cs2 O) low‐temperature water‐gas shift catalyst evolves under various H2 partial pressures in the presence/absence of a Cs promoter during thermal activation has been the subject of the present investigation. Read the full text of their Research Article at 10.1002/cmtd.202200015 . Abstract : "… This is a real boon for the technique as it shows that we can safely translate the intricate analysis of powder X‐ray to X‐ray diffraction computed tomography data…" Find out more about the story behind the front cover research at 10.1002/cmtd.202200015 .